2014
DOI: 10.1186/1471-2407-14-746
|View full text |Cite
|
Sign up to set email alerts
|

“We talk it over” - mixed-method study of interdisciplinary collaborations in private practice among urologists and oncologists in Germany

Abstract: BackgroundUtilisation of multidisciplinary teams is considered the best approach to care and treatment for cancer patients. However, the multidisciplinary approach has mainly focused on inpatient care rather than routine outpatient care. The situation in private practice care and outpatient care is gradually changing. We aimed to 1), investigate interdisciplinary cooperations in the care of tumor patients among urologists and oncologists in the community setting, 2), establish an estimate of the prevalence of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…In a study on GPs' involvement in cancer care in Germany (OHa-Oncology in General Practice), we also found slow or non-existent information sharing to be an issue (Dahlhaus, Vanneman, Guethlin, Behrend, & Siebenhofer, 2014). In a study on the cooperation of urologists and oncologists (IBuTu-Interdisciplinary Health Care of Urological Tumours), we found that both formal and informal cooperation structures were considered important for a well-functioning cooperation relationship (Beermann, Chakkalakal, Muckelbauer, Weißbach, & Holmberg, 2014).…”
Section: Introductionmentioning
confidence: 77%
See 4 more Smart Citations
“…In a study on GPs' involvement in cancer care in Germany (OHa-Oncology in General Practice), we also found slow or non-existent information sharing to be an issue (Dahlhaus, Vanneman, Guethlin, Behrend, & Siebenhofer, 2014). In a study on the cooperation of urologists and oncologists (IBuTu-Interdisciplinary Health Care of Urological Tumours), we found that both formal and informal cooperation structures were considered important for a well-functioning cooperation relationship (Beermann, Chakkalakal, Muckelbauer, Weißbach, & Holmberg, 2014).…”
Section: Introductionmentioning
confidence: 77%
“…This has been shown to be the case across different health care systems, such as in the US (Gandhi et al, 2000;Shen et al, 2015), Australia (Jefford et al, 2008;Lizama et al, 2015) and UK (Farquhar et al, 2005). In a study on the cooperation of urologists and oncologists (IBuTu-Interdisciplinary Health Care of Urological Tumours), we found that both formal and informal cooperation structures were considered important for a well-functioning cooperation relationship (Beermann, Chakkalakal, Muckelbauer, Weißbach, & Holmberg, 2014). In a study on the cooperation of urologists and oncologists (IBuTu-Interdisciplinary Health Care of Urological Tumours), we found that both formal and informal cooperation structures were considered important for a well-functioning cooperation relationship (Beermann, Chakkalakal, Muckelbauer, Weißbach, & Holmberg, 2014).…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations